2022
DOI: 10.1155/2022/6353909
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biodegradable Delivery Systems Containing Novel 1,2,4-Trioxolane Based on Bacterial Polyhydroxyalkanoates

Abstract: In this work, delivery systems in the form of microparticles and films containing 1,2,4-trioxolane (ozonide, OZ) based on polyhydroxyalkanoates (PHAs) were developed. Main systems’ characteristics were investigated: the particle yield, average diameter, zeta potential, surface morphology, loading capacity, and drug release profile of microparticles, as well as surface morphology and release profiles of OZ-containing films. PHA-based OZ-loaded microparticles have been found to have satisfactory size, zeta poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…We have previously shown that PHA microparticles and films containing synthetic ozonide peroxide (OZ) inhibit cell growth and proliferation. The viability of HeLa cells when adding OZ-containing samples was 2-10%, compared to the control group (blank films and microparticles prepared from P3HB and P3HB/3HV), where the cell viability was at the level of 90% [104]. On the whole, in a culture of HeLa cells, the cytostatic efficacy of the 5-fluorouracil loaded in PHAs microparticles is shown.…”
Section: Antibacterial and Antitumor Efficacy Of Drug-loaded Pha Micr...mentioning
confidence: 87%
“…We have previously shown that PHA microparticles and films containing synthetic ozonide peroxide (OZ) inhibit cell growth and proliferation. The viability of HeLa cells when adding OZ-containing samples was 2-10%, compared to the control group (blank films and microparticles prepared from P3HB and P3HB/3HV), where the cell viability was at the level of 90% [104]. On the whole, in a culture of HeLa cells, the cytostatic efficacy of the 5-fluorouracil loaded in PHAs microparticles is shown.…”
Section: Antibacterial and Antitumor Efficacy Of Drug-loaded Pha Micr...mentioning
confidence: 87%
“…Vennerstrom et al reported in 2008 that OZ277 generated the ineffectual OZ381 173a and OZ397 173b carbinol metabolites (IC 50 = 10 −6 mol/L against the P. falciparum strain CQ‐resistant K1) to hydrolysis by human liver microsome, of 4a (OZ277, IC 50 = 2.54 × 10 −9 mol/L) 232,233 . It has been found that ozonides OZ277 and OZ418 are able to inhibit α‐coronavirus NL63, β‐coronavirus OC43, and SARC‐CoV‐2 234 . Extensive research also revealed that the spiroadamantane ring on the final staging point was hydroxylated.…”
Section: Some Antimalarial Endoperoxide Moieties Other Than 124‐triox...mentioning
confidence: 99%
“…232,233 It has been found that ozonides OZ277 and OZ418 are able to inhibit α-coronavirus NL63, β-coronavirus OC43, and SARC-CoV-2. 234 Extensive research also revealed that the spiroadamantane ring on the final staging point was hydroxylated. As a result of the same sterically compromised composition of such ozone products, the spiroadamantane chain is unable to react with Fe (II) within parasites, preventing their medicinal effect.…”
Section: Trioxolane-polyamine Conjugatesmentioning
confidence: 99%
“…The uniqueness of this class of materials is that it is possible to obtain copolymers of various compositions with different physical and mechanical properties. It is known that the inclusion of such monomers as 4-hydroxybutyrate (4HB), 3-hydroxyvalerate (3HV), and 3-hydroxyhexanoate (3HHx) affects the physical and mechanical properties [ 47 , 48 , 49 ]. Features of the microstructure and surface relief of PHA samples of different monomeric composition depend on the inclusion of these monomers, which affect the biological properties [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%